Teacher Strategies in Internalized Religious Values Through Islamic Religious Education Learning - Tamyis, Tamyis (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This research aims to analyze teachers' strategies in internalizing religious values ​​through Islamic Religious Education learning at MI Tarbiyatul Athfal East Lampung Regency, Lampung Province, Indonesia. This research uses a qualitative descriptive approach to gain an in-depth understanding of the strategies implemented by teachers in strengthening students' religious character. Data was obtained from primary sources, including PAI teachers, madrasa heads, and students, as well as secondary sources such as learning implementation plans, assessment documents, and school activity records. Data collection techniques consist of classroom observations, in-depth interviews, and documentation studies. The data were analyzed using an interactive model involving data reduction, data presentation, and drawing conclusions to ensure systematic interpretation of the findings. The research results show that teachers apply integrative strategies in internalizing religious values. These strategies include value-based learning planning, use of participatory and contextual teaching methods, implementation of religious habituation programs, teacher examples, and ongoing behavioral evaluation. These strategies have been proven to make a positive contribution to the development of students' religious character, especially in improving religious discipline, honesty, responsibility, and social attitudes. However, the effectiveness of this strategy is still influenced by several external factors, such as variations in students' family backgrounds and the increasing influence of digital media in everyday life. This research contributes to the development of discourse on the internalization of values ​​in Islamic education by offering an integrative learning model. Practically, these findings provide a framework that can be applied to strengthen character education in Islamic elementary schools.